Developing an improvement culture within nonprofit organizations: a grounded theory case of Saudi Arabia - Almaiman, Sulaiman Abdullah Saleh; McLaughlin, Patrick (IBMA, 2018)
It has been confirmed that organizational culture (OC) has a significant impact on facilitating continuous improvement (CI), although it is not clear yet how this impact can be achieved. On the other hand, nonprofit organizations (NPOs) struggle mainly in sustaining resources and increasing the quality of the services they provide. Nonetheless, NPOs contribute remarkably to economies and civilisation. They deserve research attention, and studies done on CI suggest it to be holistically beneficial. Therefore, this paper has selected Saudi NPOs for their social setting to explore the influence of facilitating CI. The approach of grounded theory has been employed, using qualitative data, to construct a reality based on participant perspectives. The thirty-one interviews that were conducted at thirteen organizations revealed many lower level cultural aspects. These aspects were evolved, during five focus groups, into six higher-level themes. The findings can be used by leaders to create desired change.
Keywords: Organizational Culture; Continuous Improvement; Nonprofit Originations; Saudi Arabia